EFEKTIVITAS MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA COMIC STRIPS TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA SISWA KELAS IV SD - Futuh Dwi Komala; Susilo Tri Widodo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aimed to (1) determine the difference in students’ learning outcomes between those taught using the Problem Based Learning (PBL) model assisted by digital comic strip media and those taught using conventional methods, (2) assess the improvement in learning outcomes in each class, and (3) evaluate the effectiveness of the PBL model assisted by digital comic strip media in achieving learning mastery in Civic Education. This research used a quantitative approach with a quasi-experimental design, specifically the Nonequivalent Control Group Design. The sample consisted of 36 fourth-grade students from two elementary schools, selected using cluster random sampling. Data were collected using multiple-choice tests (pretest and posttest), observation, and documentation. Data analysis techniques included prerequisite tests (normality and homogeneity), an independent sample t-Test, N-Gain analysis, and a Z-test to measure learning mastery effectiveness. The results showed a significant difference in learning outcomes between the experimental and control classes, with the experimental class achieving higher posttest scores. The N-Gain results indicated a “less effective” improvement in the experimental class and an “ineffective” category in the control class. Furthermore, the proportion of students achieving mastery in the experimental was not statistically significant based on the Z-test. It is concluded that the PBL model assisted by digital comic strip media has a positive impact on improving students’ learning outcomes, although its effectiveness in achieving statistical mastery is not yet optimal.